Scenario of her fruit weevil Auheus himalayanus Voss (Coleoptera: Curculionidae) incidence in her-based cropping system (Indian Journal of Arid Horticulture, 2016)
The ber fruit weevil, Aubeus himalayanus, is an emerging pest of ber in arid and semi-arid regions of India. It was recorded as a new pest of ber for the first time from Andhra Pradesh (Gour and Sriramulu, 1994). Later, it was also found in Rahuri, Maharashtra, and Jobner, Rajasthan (Anonymous, 2003); Karnataka (Balikai et al., 1998); and more recently in Bikaner (Karuppaiah et al., 2010). The pest infestation occurs in all fruit stages; however, it is most prevalent in pea to pebble-sized fruits. The pest feeds only on the seed of developing fruit, which arrests further fruit development. In severe cases, it can cause damage ranging from 23.63% to 43.28% (Karuppaiah et al., 2014). Currently, the fruit weevil is managed mainly using synthetic insecticides, and the use of bio-pesticides is very limited. Summer ploughing is an ecologically sound cultural method that minimizes the fruit weevil by destroying the residual pupae. It is also a recommended cultural practice against tephritid fruit flies of ber.
Keywords: Experimental Block; ecologically; Karuppaiah